Peran Nilai Tsiqah dalam Konseling Moral untuk Membangun Budaya Antikorupsi - Fatimah; Ridara, Rina; Umairah, Hidayah; Zahrina; Niar (Insight Journal, 2025)
The value of tsiqah is a fundamental concept in the classical Islamic scholarly tradition, particularly in the science of hadith, which emphasizes the credibility, honesty, and integrity of narrators. In the modern social context, this value holds significant relevance as a moral principle that can be actualized to address various crises of public trust, including the widespread issue of corruption. This study aims to examine the meaning, relevance, and role of tsiqah in moral counseling as a means of shaping anti-corruption character in both individuals and institutions. The research method employed is qualitative-descriptive with a literature study approach that reviews classical and contemporary sources, including hadith collections, academic works, and relevant scientific journals. Data were analyzed using content analysis techniques to explore the values of tsiqah, its role in fostering integrity, and its application in moral counseling processes focused on preventing corruption. The findings indicate that tsiqah is not merely a scholarly principle but also an ethical foundation capable of building moral awareness, strengthening integrity-based leadership, and promoting social behavior free from corruption. Through moral counseling grounded in the value of tsiqah, individuals can be guided to develop self-awareness, social responsibility, and a commitment to honesty. This study concludes that the actualization of tsiqah in moral counseling is an ethical and contextual strategy to foster a sustainable anti-corruption culture in modern society.